Gain-of-Function STAT1 Mutation With Familial Lymphadenopathy and Hodgkin Lymphoma - Sarah E. Henrickson; Sarah E. Henrickson; Joseph G. Dolan; Lisa R. Forbes; Lisa R. Forbes; Alexander Vargas-Hernández; Alexander Vargas-Hernández; Shiho Nishimura; Satoshi Okada; Leslie S. Kersun; Garrett M. Brodeur; Jennifer R. Heimall (Frontiers Media S.A., 2019)
In this report, we describe a novel T437N STAT1 mutation found in a mother and 3 of her 4 children which we demonstrate yields gain-of-function. All of the four patients with the T437N STAT1 mutation experienced lymphadenopathy. However, two of the children developed Nodular Lymphocyte Predominant Hodgkin Lymphoma (NHLPL) and have responded to chemotherapeutic regimens. The fourth sibling had neither the STAT1 variant nor lymphadenopathy or malignancy. To our knowledge this is the first description of a potential association between STAT1 GOF mutations and lymphoma development.